Subdural grid and depth electrode monitoring in pediatric patients. (April 2017) - Skoch, Jesse; Adelson, P. David; Bhatia, Sanjiv; Greiner, Hansel M.; Rydenhag, Bertil; Scavarda, Didier; Mangano, Francesco T.
Summary: Invasive electroencephalographic monitoring with implantable subdural electrodes and intraparenchymal depth electrodes has become a basic tenet of epilepsy surgery. Improved localization of epileptic foci justifies the secondary procedure and monitoring period in many patients. Informed use of invasive monitoring in conjunction with imaging and functional studies makes epilepsy surgery a smaller, safer, and more effective endeavor. Herein we review the history, indications, implementation, and foreseeable future of grid, strip, and depth electrode use.